Stable dehydroaromatization of ethane over Zn ion exchanged MFI type galloaluminosilicate zeolite. (1st December 2021) - Inoue, Reina; Miyake, Koji; Hotta, Yuma; Xinyu, Li; Yashiro, Ryoga; Hirota, Yuichiro; Uchida, Yoshiaki; Miyamoto, Manabu; Oumi, Yasunori; Yi Kong, Chang; Nishiyama, Norikazu
Graphical abstract: Highlights: Zn ion doped MFI type galloaluminosilicate zeolite (Zn/[Ga, Al]-MFI) was synthesized. Zn/[Ga, Al]-MFI was the ideal catalyst for stable ethane dehydroaromatization. The acidity tuned by a partial substitution of Ga for Al suppressed a coke formation. Abstract: Ethane dehydroaromatization (EDA) reaction is one of the promising processes to meet the growing demand of aromatics in the future. Zn ion exchanged MFI type aluminosilicate zeolite (Zn/[Al]-MFI) shows high activity on EDA reaction. Zn ion and Brønsted acid derived from Al sites contribute to the high activity on EDA reaction, but excess strong acid sites promote coke formation, leading to rapid deactivation. Herein, we have developed a new synthesis method for Zn ion exchanged MFI type galloaluminosilicate zeolite (Zn/[Ga, Al]-MFI). The coke formation was suppressed by partially substituting Al with Ga since acidity derived from Ga sites are weaker than that derived from Al sites. Zn/[Ga, Al]-MFI was the ideal catalyst to achieve both high catalytic activity and stability on EDA reaction. Our work provides a new design direction of zeolite catalysts on EDA reaction, which can contribute to the progress on the transformation of light alkanes to value-added chemicals.